THE INFLUENCE OF PROPHETIC LEADERSHIP ON ENGAGEMENT MEDIATED BY ORGANIZATIONAL CLIMATE AMONG TEACHERS AT DELI SERDANG ISLAMIC BOARDING SCHOOLS - Andika Rahmadani Ginting; Risydah Fadilah; Yudistira Fauzy Indrawan (International Journal of Cultural and Social Science, 2026)
This study examines the effect of prophetic leadership on teachers’ engagement through the mediation of organizational climate in Islamic boarding schools (Pondok Pesantren) in Deli Serdang Regency. Using a quantitative explanatory design, data were collected from 397 teachers selected through purposive sampling. Questionnaires with a Likert scale were analyzed using Structural Equation Modeling (SEM) with SmartPLS 3.0. The results indicate that prophetic leadership has a positive and significant effect on organizational climate but does not directly influence teachers’ engagement. In contrast, organizational climate has a positive and significant effect on engagement and serves as a significant mediator in the relationship between prophetic leadership and engagement. These findings suggest that prophetic leadership enhances teachers’ engagement indirectly by fostering a positive organizational climate. Leaders who uphold prophetic values such as honesty, exemplary conduct, moral guidance, and a clear religious vision are better able to create a supportive work environment and strengthen teachers’ commitment to their professional roles.